The Strategic Role of Leadership Agility and Entrepreneurial Orientation in Fostering Innovation Ambidexterity and Enhancing Competitive Advantage - Winarsih, Tutik; Suhartini, Dwi; Handayani, Wiwik; Yuniningsih, Yuniningsih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research delves into how leadership agility and entrepreneurial orientation impact innovation ambidexterity and competitive advantage strategically, taking into consideration both direct and indirect effects. Using a quantitative approach with an explanatory research design, the study conducted a survey of all 90 small culinary businesses in Surabaya City using a census sampling method. Data collection was done through structured questionnaires and analysis was performed using SmartPLS 3.0. The results indicate that both leadership agility and entrepreneurial orientation have a significant positive effect on innovation ambidexterity. Furthermore, these antecedent variables exert a substantial impact on competitive advantage. Notably, innovation ambidexterity plays a mediating role, reinforcing its function as a critical mechanism linking internal capabilities to strategic outcomes. The originality of this study is in its detailed examination of small food businesses, a sector that has not been fully explored. It sheds light on how these companies can use their internal strengths to improve their competitive edge. This research adds to the conversation about Sustainable Development Goals (SDGs), with a specific focus on SDG 8 (Promoting Jobs and Economic Growth) and SDG 9 (Encouraging Industry, Innovation, and Infrastructure). It emphasises the role of flexible leadership and entrepreneurial planning in promoting creativity and resilience in small businesses.